KnowledgeBoat Logo

Mathematics

Simplify the following :

cosec (90° - θ) sin (90° - θ) cot(90° - θ)cos (90° - θ) sec (90° - θ) tan θ+cot θtan (90° - θ).\dfrac{\text{cosec (90° - θ) sin (90° - θ) cot(90° - θ)}}{\text{cos (90° - θ) sec (90° - θ) tan θ}} + \dfrac{\text{cot θ}}{\text{tan (90° - θ)}}.

Trigonometrical Ratios

13 Likes

Answer

We know that,

sin (90° - θ) = cos θ
cos (90° - θ) = sin θ
sec (90° - θ) = cosec θ
cosec (90° - θ) = cot θ
cot (90° - θ) = tan θ.

Substituting values in equation, we get :

cosec (90° - θ) sin (90° - θ) cot(90° - θ)cos (90° - θ) sec (90° - θ) tan θ+cot θtan (90° - θ)sec θ cos θ tan θsin θ cosec θ tan θ+cot θcot θ1cos θ×cos θ×tan θsin θ×1sin θ×tan θ+11+12.\Rightarrow \dfrac{\text{cosec (90° - θ) sin (90° - θ) cot(90° - θ)}}{\text{cos (90° - θ) sec (90° - θ) tan θ}} + \dfrac{\text{cot θ}}{\text{tan (90° - θ)}} \\[1em] \Rightarrow \dfrac{\text{sec θ cos θ tan θ}}{\text{sin θ cosec θ tan θ}} + \dfrac{\text{cot θ}}{\text{cot θ}} \\[1em] \Rightarrow \dfrac{\dfrac{1}{\text{cos θ}} \times \text{cos θ} \times \text{tan θ}}{\text{sin θ} \times \dfrac{1}{\text{sin θ}} \times \text{tan θ}} + 1 \\[1em] \Rightarrow 1 + 1 \\[1em] \Rightarrow 2.

Hence, cosec (90° - θ) sin (90° - θ) cot(90° - θ)cos (90° - θ) sec (90° - θ) tan θ+cot θtan (90° - θ)\dfrac{\text{cosec (90° - θ) sin (90° - θ) cot(90° - θ)}}{\text{cos (90° - θ) sec (90° - θ) tan θ}} + \dfrac{\text{cot θ}}{\text{tan (90° - θ)}} = 2.

Answered By

6 Likes


Related Questions